TINJAUAN PERJANJIAN ANTARA PEGURUS PROVINSI PERSATUAN TENIS MEJA SELURUH INDONESIA KALIMANTAN TIMUR DENGAN ATLET TENIS MEJA - Winda Dwi Rahayu (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTThis author is intended to explain in detail the matters that become legal issues. The provincial board of the all Indonesian table tennis association, East Kalimantan, has the maximum desire or target for the East Kalimantan table tennis athletes to be more accomplished in achieving maximum targets that can make East Kalimantan province proud and can also scent the red and white flag in the international arena. The provisions of the agreement making related to article 1313 of the Civil Code which states that an agreement is an act whereby one or more people bind themselves to one or more people. However, there are problems that occur, de facto there are still many provincial administrators of table tennis associations throughout Indonesia who do not meet the conditions in the agreement and do not comply with the agreement when the agreement was made, causing an achievement. Where in this case the athlete is the most disadvantaged. Regarding this, the writer needs to be careful with regard to: (1) What are the terms of the agreement between the Provincial Management of the Indonesian Table Tennis Association, East Kalimantan, and the Table Tennis Athletes; (2) What are the legal consequences for the parties who do not carry out the contents of the agreement between the Provincial Administrators of the Indonesian Table Tennis Association, East Kalimantan and the Table Tennis Athletes. The type of research used in this research is Normative Juridical research and the statutory approach (Statue Approach) and conceptual (Conceptual Approach). The results of this study indicate the terms of the agreement making that the agreement made has been determined unilaterally by the PTMSI Pengprov without involving the athlete, that is, if an athlete violates the agreement, he will be subject to sanctions in the form of a PTMSI Decree (SK) Article 67 of 2018 concerning Articles of Association and Budget. PTMSI Household Basics, whereas if the provincial government does not carry out the contents of the agreement, it will be enforced in accordance with the applicable sanctions laws and regulations.Keywords: Agreement, Table Tennis Athletes.